شائعة العنف من وجهة نظر أساتذة الجامعة وعلاقتها ببعض المتغيرات - منصور الحلــو بثينة (Al-Adab Journal, 2018)
Terrorism is considered to be as an international phenomenon, which is available in any society all over the world. One of the characteristics of terrorism is violation, which is the subject of all fields in life politics, religion,… etc. nowadays. It can be shown as physical or morale violation. The tools of violence are different from each other. One of these tools which is used in the morale violence is RUMOR, it is the most important tool which has a powerful effect on the society. The present paper tackles with the effect of rumor on the highest rank of the society which is the rank of instructors of the universities. It specifies as well the most powerful kind of rumor which affects them.